Pengembangan kurikulum bahasa Arab di Madrasah berbasis karakter - Nasution, Sahkholid (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
Moral decadence of the nation today are very concerned. Not only the students in the school, but also students in Madrasah, the postscript learning Islamic education and Arabic language more than in school. Therefore, the cultivation of students' character should be done through the development of the curriculum in all subjects including Arabic lessons. This paper aims to describe how the Arabic language curriculum development to shape the character of the students. The methodology used was a qualitative approach with descriptive-analytic method. Among its conclusions: (1). Selection of teaching materials from the texts that are full of character values. (2). Mahfuzhat maximize learning. (3). The routine of Arabic. (4). Modeling and (5). Conditioning